Single Cell Transcriptome Helps Better Understanding Crosstalk in Diabetic Kidney Disease - Du, Chunyang; Ren, Yunzhuo; Li, Guixin; Yang, Yan; Yan, Zhe; Yao, Fang (Frontiers in Medicine, 2021)
Years of research revealed that crosstalk which extensively exists among kidney cells, cell factors and metabolites played an important role in the development of diabetic kidney disease (DKD). In the last few years, single-cell RNA sequencing (scRNA-seq) technology provided new insight into cellular heterogeneity and genetic susceptibility regarding DKD at cell-specific level. The studies based on scRNA-seq enable a much deeper understanding of cell-specific processes such as interaction among them. In this paper, we aim to review recent progress in single cell transcriptomic analyses of DKD, particularly highlighting on intra- or extra-glomerular cell crosstalk, cellular targets and potential therapeutic strategies for DKD